2003
DOI: 10.1016/s0014-5793(03)00900-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulated secretion of macrophage migration inhibitory factor is mediated by a non‐classical pathway involving an ABC transporter

Abstract: The cytokine macrophage migration inhibitory factor (MIF) is inducibly secreted by immune cells and certain other cell types to critically participate in the regulation of the host immune response. However, MIF does not contain a N-terminal signal sequence and the mechanism of MIF secretion is unknown. Here we show in a model of endotoxin-stimulated THP-1 monocytes that MIF does not enter the endoplasmatic reticulum and that MIF secretion is not inhibited by monensin or brefeldin A, demonstrating that MIF secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
170
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(181 citation statements)
references
References 52 publications
8
170
2
1
Order By: Relevance
“…JAB1 is part of the CSN, which is located in the nucleus and cytoplasm, where it can interact with MIF (Kleemann et al, 2000;Chamovitz and Segal, 2001;Bech-Otschir et al, 2002). MIF is secreted from immune cells and fibroblasts by a nonconventional export pathway bypassing the ER/Golgi apparatus (Flieger et al, 2003;Nickel, 2003). Upon protein synthesis, MIF is 'stored' in the cytosol before translocation into a secretion competent, yet unidentified, vesicular compartment (Bernhagen et al, 1993;Flieger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…JAB1 is part of the CSN, which is located in the nucleus and cytoplasm, where it can interact with MIF (Kleemann et al, 2000;Chamovitz and Segal, 2001;Bech-Otschir et al, 2002). MIF is secreted from immune cells and fibroblasts by a nonconventional export pathway bypassing the ER/Golgi apparatus (Flieger et al, 2003;Nickel, 2003). Upon protein synthesis, MIF is 'stored' in the cytosol before translocation into a secretion competent, yet unidentified, vesicular compartment (Bernhagen et al, 1993;Flieger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…MIF is secreted from immune cells and fibroblasts by a nonconventional export pathway bypassing the ER/Golgi apparatus (Flieger et al, 2003;Nickel, 2003). Upon protein synthesis, MIF is 'stored' in the cytosol before translocation into a secretion competent, yet unidentified, vesicular compartment (Bernhagen et al, 1993;Flieger et al, 2003). This latter process is dependent on an ABCA1 transporter (Flieger et al, 2003), and our current study demonstrates that JAB1 can retain MIF in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of them is related to the absence of signal peptide reported in murine, human and fish MIF sequences, as we observed in M. galloprovincialis. Thus, evidence suggested that MIF does not travel to the endoplasmic reticulum, instead it is secreted via a non-classical export pathway involving an ATP binding cassette transporter (Flieger et al, 2003). MIF is part of the growing list of cytokines, such as interleukin-1 (IL-1) and basic fibroblast growth factor (bFGF), which are released from cells by non-classical pathways.…”
Section: Discussionmentioning
confidence: 99%